MyScan barcode scanner price comparison application / Nur Sharina Abdul Mutalib - Nur Sharina, Abdul Mutalib (2016)
Barcode scanner of the price for comparison application has been in the world. However, it does not in Malaysia. Mobile barcode scanning applications can improve the daily buying decisions of millions of users. Smartphones are widely used by people today and can be used as a platform to encourage the barcode scanner. This project will bring a barcode scanner into a portable device in the Android platform. This project will develop a mobile application based on the survey that the people are the responses. Besides that, this project will develop the comparison of the prices of the product based on the supermarket. Moreover, people can make the decision to choose the lower prices of the product.